Силовой активный фильтр при работе на несимметричную и нелинейную нагрузки с управлением по оптимизационному алгоритму - Ягуп, Е.В. (Електротехніка і електромеханіка, 2017)
Статья посвящена исследованию трехфазной четырехпроводной системы электроснабжения, питающей несимметричную трехфазную и однофазную нелинейную нагрузки. Силовой активный фильтр представляет собой четырехплечевой мостовой инвертор на IGBT транзисторах. Инвертор питается от энергообменного конденсатора и инжектирует корректирующие токи через буферные реакторы. В отличие от классической системы управления, основанной на преобразованиях Кларк для напряжений и токов, в рассматриваемом варианте предложено управление источниками эталонных сигналов, априори имеющими синусоидальную форму и совпадающими с фазами питающих источников электрической энергии. Определение необходимых амплитуд эталонных сигналов составляет сущность задачи поисковой оптимизации. Оптимизация осуществляется методом деформируемого многогранника с использованием визуальной модели системы электроснабжения с силовым активным фильтром. По завершении оптимизации система приходит к оптимальному режиму, характеризующемуся полной компенсацией всех составляющих реактивной мощности. Стаття присвячена дослідженню трифазної чьотирипровідної системи електропостачання, що живить несиметричне трифазне і нелінійне однофазне навантаження. Силовий активний фільтр являє собою чотириплечовий мостовий інвертор на IGBT транзисторах. Інвертор живиться від енергообмінного конденсатора і інжектує коригувальні струми через буферні реактори. На відміну від класичної системи управління, заснованої на перетвореннях Кларк для напруг і струмів, в даному варіанті запропоновано управління джерелами еталонних сигналів, які апріорі мають синусоїдальну форму і збігаються з фазами живильних джерел електричної енергії. Визначення необхідних амплітуд еталонних сигналів становить сутність пошукової оптимізації. Оптимізація здійснюється шляхом деформованого багатогранника з використанням візуальної моделі системи електропостачання з силовим активним фільтром. По завершенні оптимізації система приходить до оптимального режиму, що характеризується повною компенсацією всіх складових реактивної потужності. Purpose is to develop a method for controlling a power active filter based on search optimization using software of Mathlab package and applying this method for balancing and compensating for all components of reactive power in a three-phase system feeding unbalanced linear and nonlinear loads simultaneously. Methodology consists in the development of a visual model of the power supply system that supplies unbalanced and non-linear loads, to the connection points of which a power active filter on IGBT transistors is connected according to a parallel type scheme. We propose an algorithm for calculating the chosen optimization criterion using a visual model, linking the visual model with an optimizing program, and performing a search engine optimization process using an embedded program that implements the deformable polyhedron algorithm. Results lead to an optimal mode, which is characterized by the amplitudes of the control signals of the power active filter control system determined by the search, as well as the initial value of the voltage on the filter energy exchange capacitor. Originality lies in the fact that the proposed method of controlling the operation of the power filter makes it possible to dispense with the construction of a relatively complex filter control system based on Clark's mathematical transformations. Practical value lies in the fact that finding a quasi-steady-state optimal mode of the power supply system with a power active filter is performed automatically in the process of search optimization with a simplified control system. The above principles can be implemented in the microprocessor control system for power active filters.